EVALUATING THE EFFECTIVENESS OF PHONOPHORESIS BY PIROXICAM AND DIMETHYL SULFOXIDE FOR WOMEN’S WITH OSTEOARTHRITIS KNEE JOINT - R, Monisha; M, Manikumar; Krishnakumar, Aparna (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: Osteoarthritis (OA) is a progressive chronic disease with the loss of articular cartilage. In managing osteoarthritis, inadequate pain relief often occurs, particularly with a single non-steroidal anti-inflammatory drugs therapy. Methods: A total of 50 participants were randomly allocated into three groups, received phonophoresis with piroxicam, dimethyl sulfoxide (DMSO), and ultrasound (US) therapy with aquasonic gel. Results: On comparing, the baseline phonophoresis group with piroxicam showed significantly more pain reduction than the DMSO and US therapy. Enrolled patients in three groups have completed the study without any drawbacks. Conclusion: This study showed that phonophoresis was superior to conventional US therapy in reducing pain in patients with symptomatic knee OA of a mild to moderate degree.